Interpersonal problems and recognition of facial emotions in healthy individuals - Suslow, Thomas; Lemster, Alexander; Koelkebeck, Katja; Kersting, Anette (Frontiers in Psychiatry, 2023)
Background: Recognition of emotions in faces is important for successful social interaction. Results from previous research based on clinical samples suggest that difficulties in identifying threat-related or negative emotions can go along with interpersonal problems. The present study examined whether associations between interpersonal difficulties and emotion decoding ability can be found in healthy individuals. Our analysis was focused on two main dimensions of interpersonal problems: agency (social dominance) and communion (social closeness). Materials and Methods: We constructed an emotion recognition task with facial expressions depicting six basic emotions (happiness, surprise, anger, disgust, sadness, and fear) in frontal and profile view, which was administered to 190 healthy adults (95 women) with a mean age of 23.9 years (SD = 3.8) along with the Inventory of Interpersonal Problems, measures of negative affect and verbal intelligence. The majority of participants were university students (80%). Emotion recognition accuracy was assessed using unbiased hit rates. Results: Negative correlations were observed between interpersonal agency and recognition of facial anger and disgust that were independent of participants’ gender and negative affect. Interpersonal communion was not related to recognition of facial emotions. Discussion: Poor identification of other people’s facial signals of anger and disgust might be a factor contributing to interpersonal problems with social dominance and intrusiveness. Anger expressions signal goal obstruction and proneness to engage in conflict whereas facial disgust indicates a request to increase social distance. The interpersonal problem dimension of communion appears not to be linked to the ability to recognize emotions from facial expressions.